Pengaruh Pemberian Antidepresan Terhadap Aktivitas Fisiologi Kulit Tanaman Karet (Hevea brasiliensis Muell. Arg) Klon Pb260 dan Rrim921 - Mawaddah Putri Arisma Siregar; Rosmayati Rosmayati; Hot Setiado; Radite Tistama; Evi Julianita Harahap (Universitas Teuku Umar, 2023)
Tapping panel dryness lead production dropped significantly and can speed up rejuvenation. Then the leaf fall period can also reduce the value of the production of rubber annually. Therefore, the analysis of several physiological variables is especially important with the skin rubber plant so it can be an early indicator of the healing tapping panel dryness. The research aims to analyze the physiology of the bark on the rubber tree (Hevea brasiliensis Muell. Arg) clones PB 260 and RRIM 921 at the time of the leaf fall period were given antidepressants. This research was conducted at the Laboratory of Physiology Sungei Putih Rubber Research Centre. While hypothesis testing using T partially by using SPSS 20.0. The treatment factors were: Clones (RRIM 921 and PB 260), types of plants (healthy and tapping panel dryness), and use of formula (control and antidepresant). Parameters measured were thiol, inorganic phosphate (pi), sucrose. The results showed that the range of values Thiol bark is 0.1-0.9 mM, Pi is 4-20 mM and 24-60 mM sucrose. They are changed in accordance with the state of the plant and environmental factors.